2018
DOI: 10.1111/1556-4029.13945
|View full text |Cite
|
Sign up to set email alerts
|

Homicidal Paraquat Poisoning

Abstract: Paraquat poisoning usually results from suicide, occupational, or accidental exposure. Herein, we report a rare fatal case of homicidal paraquat poisoning. A 58‐year‐old man was poisoned by taking paraquat‐mixed medicine and wearing paraquat‐soaked underwear. In the absence of a history of paraquat exposure, the patient was misdiagnosed with pulmonary infection and scrotal dermatitis and died of respiratory failure 24 days after the initial exposure to paraquat. Ultra‐performance liquid chromatography‐tandem m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…PQ can cause fatal poisoning when absorbed via ingestion, skin contact, or inhalation. PQ poisoning has become a severe problem in some developing countries such as China [5]. Multiple organs such as liver, kidney, heart and central nervous system can be affected; but lung is the primary target of PQ [14,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PQ can cause fatal poisoning when absorbed via ingestion, skin contact, or inhalation. PQ poisoning has become a severe problem in some developing countries such as China [5]. Multiple organs such as liver, kidney, heart and central nervous system can be affected; but lung is the primary target of PQ [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple organs such as liver, kidney, heart and central nervous system can be affected; but lung is the primary target of PQ [14,20]. PQ is actively taken up in a concentration dependent manner and accumulates at particularly high levels in Clara cells and epithelial cells [5,10,13,18]. PQ poisoning initially leads to acute lung injury (ALI), and ultimately to lung fibrosis or subsequent respiratory failure, which is the most common cause of death from PQ [12].…”
Section: Introductionmentioning
confidence: 99%
“…We tried to mimic clinical features of PQ intoxication by injecting different doses of PQ to establish acute and chronic models. In clinical practice, patients who expose to high dose of PQ will pass away within a few days due to multi-organ injury or pneumonia; other patients who expose to low dose of PQ usually have no symptom at the beginning but suffer from pulmonary fibrosis later and pass away after about 1 month (Chen et al, 2019b). By using GC-TOF/MS technique following machine learning statistic methods, we observed significant metabolic features in mice serum after acute PQ intoxication while the metabolic alteration after chronic PQ intoxication was not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies have found that the concentration of PQ in severely body from low to high was stomach wall (<limit of quantitation, LOQ), cardiac blood (0.11 µg/mL), liver (0.2 µg/g), kidney (0.24 µg/g), brain (0.32 µg/g), and lung (0.49 µg/g). 5 PQ mainly accumulates in the lungs (pulmonary concentrations can be 6 to 10 times higher than those in plasma) and remains in the lungs even as blood levels begin to drop. 6 PQ poisoning can lead to multiple organ dysfunction syndrome (MODS).…”
Section: Introductionmentioning
confidence: 99%